A Novel Long Non-coding RNA, durga Modulates Dendrite Density and Expression of kalirin in Zebrafish - Sarangdhar, Mayuresh A.; Chaubey, Divya; Bhatt, Abhishek; KM, Monisha; Kumar, Manish; Ranjan, Shashi; Pillai, Beena (Frontiers in Molecular Neuroscience, 2017)
Kalirin, a key player in axonal development, nerve growth and synaptic re-modelling is implicated in many pathological conditions like schizophrenia and autism-spectrum disorders. Alternative promoters and splicing lead to functionally distinct isoforms, but the post-transcriptional regulation of Kalirin has not been studied. Here, we report a novel ncRNA, which we name durga, arising from the first exon of kalirin a (kalrna) in the antisense orientation in zebrafish. The kalrna and durga transcripts are barely detectable during early development, but steadily increase by 24hpf as the brain develops. Over-expression of durga in the zebrafish embryo led to an increase in kalrna expression. The morphology of the neurons cultured from durga injected embryos had significantly fewer and shorter dendrites. Although durga has no apparent sequence homolog in mammals, based on gene synteny, we found a non-coding RNA arising from the 5’ end of the human kalrn gene and expressed in the human neuronal cell line, SH-SY5Y. We propose that the zebrafish lncRNA durga maintains dendritic length and density through regulation of kalrn expression and this may have further implications in mammalian systems.